Pengaruh Substitusi Tepung Mocaf dan Penambahan Puree Bunga Telang Terhadap Sifat Organoleptik Roti Kukus - Atiqo Mufidatul Khoirun Nisa’; Lucia Tri Pangesthi; Sri handajani; Asrul Bahar (Lembaga Pengembangan Kinerja Dosen, 2024)
Steamed bread with the substitution of mocaf flour and the addition of butterfly pea flower puree is a steamed bread made from wheat flour and substituted with mocaf flour and added with butterfly pea flower puree. This research aims to determine the effect of mocaf flour substitution and the addition of butterfly pea flower puree on the organoleptic quality of steamed bread which includes shape, color, smell, taste and texture. This type of research is a type of experimental research. The experiment was carried out with six types of treatments consisting of 20%, 30% and 40% mocaf flour substitution and the addition of 30% and 40% butterfly pea flower puree. The data collection technique uses instruments in the form of organoleptic tests including shape, color, aroma, taste and texture of steamed bread with six different treatments. The data analysis used was two-way analysis of variance and Duncan's advanced test. The results of the research show 1) the substitution of mocaf flour has an effect on the criteria for shape, color and texture. 2) the addition of butterfly pea flower puree affects the criteria for shape, color, taste and texture. 3) the interaction between the substitution of mocaf flour and the addition of butterfly pea flower puree affects the shape and texture criteria.